2016
DOI: 10.1002/epi4.12020
|View full text |Cite
|
Sign up to set email alerts
|

Cathodal transcranial direct‐current stimulation for treatment of drug‐resistant temporal lobe epilepsy: A pilot randomized controlled trial

Abstract: SummaryObjectiveTo investigate the effect of cathodal transcranial direct‐current stimulation (c‐tDCS) on seizure frequency in patients with drug‐resistant temporal lobe epilepsy (TLE).MethodTwenty‐nine patients with drug‐resistant TLE participated in this study. They were randomized to experimental or sham group. Twenty participants (experimental group) received within‐session repeated c‐tDCS intervention over the affected temporal lobe, and nine (sham group) received sham tDCS. Paired‐pulse transcranial magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Other studies provide more robust seizure reduction results. A randomized‐controlled study of 29 patients showed that a single treatment of 18 total minutes of tDCS resulted in a 42.1% seizure reduction versus 17.0% reduction for the control group …”
Section: Less Invasive Forms Of Neurostimulationmentioning
confidence: 99%
“…Other studies provide more robust seizure reduction results. A randomized‐controlled study of 29 patients showed that a single treatment of 18 total minutes of tDCS resulted in a 42.1% seizure reduction versus 17.0% reduction for the control group …”
Section: Less Invasive Forms Of Neurostimulationmentioning
confidence: 99%
“…1. Therefore, 27 original studies met inclusion criteria and were included in this systematic review, comprising nine original sham-controlled trials [20][21][22][26][27][28][29][30][31] (Table 1) and 18 uncontrolled trials and case series/reports [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] (Tables 2 and 3). Overall, studies encompassed 328 people with epilepsy of whom 253 underwent active stimulation while 75 received sham intervention.…”
Section: Retrieved Papersmentioning
confidence: 99%
“…Zoghi et al [27] investigated the effects of a distinctive tDCS protocol in a sample of adult patients with drug-resistant temporal lobe epilepsy. A 1 mA current of cathodal stimulation targeted at the affected temporal lobe was delivered in a single session consisting of two bouts of nine minutes (18 min total) spaced by a 20-minute interval.…”
Section: Randomized Sham-controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for investigating inter-individual variability to c-tDCS lies in its potential use as an adjunct or alternative therapy to neurological populations such as those who experience excititoxicity such as Epilepsy and seizures as well as psychological populations such as those who experience anxiety disorders. A number of recent case reports and studies have reported improvements in seizure severity and frequency following trials of c-tDCS (Assenza et al, 2017;Lin et al, 2018;Tecchio et al, 2018;Tekturk et al, 2016;Yook et al, 2011;Zoghi et al, 2016) as well as fear response extinction in anxiety populations (Ganho-Ávila et al, 2019). With drugresistance a common problem in those who suffer seizures (Assenza et al, 2017;Tecchio et al, 2018), investigating adjunct non-invasive therapies such as c-tDCS is justified.…”
Section: Introductionmentioning
confidence: 99%